PENGARUH PENDIDIKAN KESEHATAN PRA BEDAH TERHADAP TINGKAT KECEMASAN PASIEN PRA BEDAH DI RUMAH SAKIT DR. OEN SURAKARTA - Diyono, Diyono; Herminto, Budi; Hana Pertiwi, Dessy (KOSALA : Jurnal Ilmu Kesehatan, 2014)
AbstractBackground. Pre-surgical patient anxiety often occur. Based on initial interviews with the majority of patients pre-surgical have anxiety with diferent level. Nursing intervention to deal the matter by providing health education although this intervention rarely give at the first day surgical period as a routine during the day prior to this it was only done as a routine and its effectiveness has not been investigated. The purpose of the study. (1) determine the level of anxiety patient’s pre-surgery before being given pre-surgical health education. (2) determine the level of patient anxiety pre-surgery after being given a pre-surgical health education. (3) determine the effect of pre-surgical health education to the patient's level of anxiety pre-surgery at the Hospital Dr. Oen Surakarta Research Design. This study was a quasi-experimental study (quasi exsperiment) using all responden preoperative patients who were treated at the Hospital Dr. Oen Surakarta. The sampling technique used was purposive sampling and with used Seruni and Soka Ward’s Hospital Dr. Oen Surakarta. measure was a questionnaire containing 20 statements. The data collected were analyzed by paired t-dependent test used SPSS for Windows series 18. The results of the study. (1) the average value of patient anxiety before given health education 13.33, median 14.00, mode of 14 and a standard deviation of 2,690. (2) the average value of the patient's pre-surgical anxiety after being given a pre-surgical health education 9,000, median 9,000, mode 9,000 and standard deviation 2,360. Conclusion pre-surgical health education impact significantly reduce anxiety by t-test result of 0.000.Keywords : Health Education, Pre Surgery, Anxiety Levels